Single-Layer Drying Behavior of Red Chili - Junaedi Muhidong; Supratomo Supratomo; Nur Ftiri Ramadhani (agriTECH, 2012)
This study was designated to determine the best model that could represent the behavior of the moisture content of cut red-chili, Tombak variety, during the single layer drying process. A Tray Dryer Model EH-TD-300 Eunha Fluid Science was used to support the experiment. The dryer was constructed to flow the drying-air parallel with the crop observed. Three levels of drying air velocity (1.0 m/s, 1.5 m/s, and 2.0 m/s) were applied under a constant drying air temperature of 47oC. The average relative humidity (RH) in the drying chamber during the drying period was around 39%. The results of this study strongly suggested that the Hii et al. (2008) model, MR = 0.76832.exp(-0.06607.t1.43089) + 0.25351.exp(-0.06881.t1.43089) and MR = 0.76758.exp(-0.10141.t1.47651) + 0.30562.exp(-0.10018.t1.47651),  were the best model in predicting the moisture behavior of the cut chili, Tombak variety, across the elapsed drying time when the drying air velocities were set to 1.5 m/s and 2.0 m/s, respectively. However, the Diffusion Approach model, MR = -0.02821.exp(0.01340.t) + (1.02821)).exp(-0.107576.t), was observed to be the best model at the drying air velocity of 1.0 m/s.